Ultrafluorogenic Coumarin–Tetrazine Probes for Real‐Time Biological Imaging1. Issue 29 (10th June 2014) - Meimetis, Labros G.; Carlson, Jonathan C. T.; Giedt, Randy J.; Kohler, Rainer H.; Weissleder, Ralph
Abstract We have developed a series of new ultrafluorogenic probes in the blue‐green region of the visible‐light spectrum that display fluorescence enhancement exceeding 11 000‐fold. These fluorogenic dyes integrate a coumarin fluorochrome with the bioorthogonal trans‐cyclooctene(TCO)–tetrazine chemistry platform. By exploiting highly efficient through‐bond energy transfer (TBET), these probes exhibit the highest brightness enhancements reported for any bioorthogonal fluorogenic dyes. No‐wash, fluorogenic imaging of diverse targets including cell‐surface receptors in cancer cells, mitochondria, and the actin cytoskeleton is possible within seconds, with minimal background signal and no appreciable nonspecific binding, opening the possibility for in vivo sensing.